2016
DOI: 10.1016/j.trd.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

External costs of electric vehicles

Abstract: Electric vehicles (EV) are often considered a promising technology to decrease external costs of road transport. Therefore, main external cost components are estimated for EV and internal combustion engine vehicles (ICEV). These include costs of accidents, air pollution, climate change, noise, and congestion. All components are estimated over the product lifetime and, where appropriate, differentiated according to fuel type, vehicle size as well as emission location and time. The advantage of this differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(50 citation statements)
references
References 50 publications
1
48
0
1
Order By: Relevance
“…The main congestion cost involves time losses and speed-dependent fuel losses. From a study by Jochem and coworkers [64], it is was analyzed that the increase in E4Ws will not resolve the issue, but it will almost be the same as the prevalence of gasoline cars. In the literature [65,66], it was found that the majority of the E4Ws owners already possess a gasoline car, so gasoline cars are not substituted.…”
Section: Congestion Costmentioning
confidence: 99%
“…The main congestion cost involves time losses and speed-dependent fuel losses. From a study by Jochem and coworkers [64], it is was analyzed that the increase in E4Ws will not resolve the issue, but it will almost be the same as the prevalence of gasoline cars. In the literature [65,66], it was found that the majority of the E4Ws owners already possess a gasoline car, so gasoline cars are not substituted.…”
Section: Congestion Costmentioning
confidence: 99%
“…Apart from reduced carbon dioxide emissions, electric vehicles decrease oil dependency, noise, and local air emissions. Overall, the external effects of these emissions are not always decreased by introducing electric vehicles …”
Section: Socioeconomic Factors and Flexible Loads In Energy Modelsmentioning
confidence: 99%
“…Overall, e-bikes are considered as a promising technology to reduce the external costs of transport, including traffic noise and air pollution effects [4]. As noted by Jones et al [5], e-bikes could also help to increase accessibility for people who are unable or not willing to use conventional bicycles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Lifecycle analysis demonstrates that riding e-bikes is also more environmentally friendly that driving cars [19,20]. On the other hand, electric vehicles are overall seen as a promising technology to decrease several road transport externalities [4], including the external costs of congestion, air pollution, traffic noise and climate change related effects assuming electric two-wheelers can penetrate the market at a large scale [21].…”
Section: Introductionmentioning
confidence: 99%